Stage IV endometrial carcinoma: a case report on multiple biomarkers and the emerging role of immunotherapy - Joshi, Advait; Benyarko, Ato Kwamena; Savaliya, Bansi; Duong, Y. Vo Nhu; Himaid, Abdullah; Lade, Ananya; Jude Lewis, Magnus; Tejaswi Gunti, Anuhya; Simsek, Bahadir; Khillan, Ratesh (International Journal of Research in Medical Sciences, 2024)
Endometrial carcinoma (EC) is a common cancer with a poor prognosis in advanced stages. Despite recent development in therapies, the optimal choice for Stage IV EC with multiple mutations remains debated. Immunotherapy has come up as a promising approach, particularly targeting the PI3K/AKT/mTOR pathway, which is associated with aggressive disease. A 68-year-old African American female with a history of diabetes, hypertension, and postmenopausal bleeding was diagnosed with Stage IV B serous type endometrial carcinoma. Imaging revealed lung and lymph node metastases. The patient received 9 cycles of carboplatin and paclitaxel followed by a radical hysterectomy. Tumour profiling revealed HER2/neu amplification, PIK3CA, and TP53 mutations. Despite microsatellite stability (MSS) and proficient mismatch repair (pMMR), she was started on pembrolizumab (200 mg every 3 weeks) and lenvatinib (20 mg daily). The patient is currently in her third cycle and responding well to treatment. This case highlights the potential of immunotherapy in advanced EC with multiple biomarkers. Although pembrolizumab was initially approved for MSI-H/dMMR cases, its combination with lenvatinib has shown efficacy in pMMR/MSS patients. The case underscores the need for personalised treatment strategies based on molecular profiling, with emerging therapies targeting HER2, TP53, and PIK3CA.